TRANSPLANTATION OF ALLOGENIC ADIPOSE-DERIVED STEM CELL IMPROVE URETHRAL MUSCLE-COLLAGEN RATIO AFTER VAGINAL DISTENSION - Yudiana, I Wayan; Hardjowijoto, Sunaryo; Alif, Sabilal; Purwati, Purwati; Sandhika, Willy; Budiono, Budiono (Indonesian Journal of Urology, 2014)
Objective:To investigate the effects of allogenic adipose-derived stem cell (ADSC) transplantation on urethral tissue regeneration after vaginal distension in a rat model.Material & Method:32 female wistar rats underwent vaginal distension (VD) for 4 h. Subsequently, PKH-labeled ADSCs (2 x 105 in 200 µl PBS, ADSC group, n = 18) or PBS (200 µl, placebo group, n = 18) were injected into periurethral tissue. Two and four weeks following transplantation (ADSC or PBS), voiding behavior (frequency) and muscle-collagen ratio of urethral tissue were measured to evaluate urethral sphincter regeneration. Data were analysed by paired-t test, one-way ANOVA and post hoc LSD.Results:Mean voiding frequency was significantly different in the ADSC group at two weeks (p<0.0001), but not significantly different at four weeks (p=0.448) when compared with the placebo group.Masson’s trichrome staining revealed that the muscle-collagen ratio of urethral tissue was not significantly different between study groups at two or four weeks (p=0.053 or p=0.166 respectively). Muscle-urethral ratio was more specific showing a significant difference at two weeks (p=0.043). There were significant differences about muscle-collagen or muscle-urethral ratio between control and placebo groups (p<0.05), whereas between control and ADSC groups no significant difference was observed (p>0.05).Conclusion:ADSC transplantation promotes urethral muscle-collagen ratio with development of striated muscle after vaginal distension, so that can improve voiding behavior in a rat model.Keywords:Adipose-derived stem cell, vaginal distension, rat-SUI model, muscle-collagen ratio, voiding stain on paper.